Evaluación de la gestión de riesgos al sistema de información S/4 HANA en empresas del sector financiero colombiano (2020)
Risk management in the SAP S / 4 HANA information system is made up of a methodological framework, the alignment of the system and its risks with the different processes it supports, and the implementation of a cost / effective approach maximizing value. of the system and the support of a technological tool that allows management to quickly and systematically manage said risk system. If these activities are followed rigorously, it is possible to affirm that the company has a risk management system for SAP HANA, organized, structured and informed.